Hubungan Tingkat Pengetahuan Ibu dengan Pemberian Imunisasi Dasar Campak di Kelurahan Balai Gadang Wilayah Kerja Puskesmas Air Dingin Kota Padang - Addina Fitri Islami; Rosfita Rasyid; Husnil Kadri (Majalah Kedokteran Andalas, 2021)
The lowest immunization coverage in  Padang is in area of Puskesmas Air Dingin Padang. Mother’s knowledge is one of the factor that influence the provision of immunization. Objectives: To determined correlation between mother’s knowledge of measles immunization and provision of measles immunization in area of Puskesmas Air Dingin Padang. Methods: This was an analytic study with cross-sectional design. The population were all of mothers with babies age 9-48 months in the area of Puskesmas Air Dingin Padang. The 139 of samples were taken by purposive sampling. Data were collected by interviews using questionnaires. Computerized data processing and analysis permormed by Chi-square test. Results: This study obtained 59,7 % of respondents gave measles immunization to their childen and 89,9% of respondents have sufficient knowledge about measles immunization. There was significant correlation between two variables (p=0,001). Conclusion: There is a significant correlation between mother’s knowledge of measles immunization and provision of measles immunization in Balai Gadang area of Puskesmas Air Dingin Padang, therefore needs to be improved counseling about measles and measles immunization to the community.